Soil carbon stocks in natural and man-made agri-hortisilvipastural land use systems in dry zones of Southern India - NAGARAJA, M. S.; BHARDWAJ, A. K.; REDDY, G.V. P.; PARAMA, V.R. R.; KAPHALIYA, B. (Journal of Soil and Water Conservation, 2020)
A study was undertaken to assess the soil carbon stocks in 0-50 cm soil depth, under natural and man-made land use systems in the eastern dry zones of Karnataka in India. The carbon (C) stocks in soils ranged from 26.46 t ha-1 in dry land agricultural systems (without manure) to 89.20 t ha-1 in a mixed forest. Among natural systems, mixed forest (89.20 t ha-1) and ungrazed grassland (71.78 t ha-1) recorded higher levels of C stock than other systems, while grazing in grassland and litter removal in teak plantations correlated to reduced carbon stocks to 39.32 and 32.74 t ha-1, respectively. Intensively managed horticultural systems namely, grapes plantation (85.52 t ha-1) and pomegranate plantation (78.78 t ha-1) maintained higher levels of C stock. However, agricultural systems recorded moderate to lower levels. Total carbon stocks in top 0-50 cm soils of agricultural systems was in the order: irrigated lands with manure application (52.77 t ha-1) > irrigated lands without manure application (44.47 t ha-1) > dry lands with manure application (37.79 t ha-1) > dry lands without manure application (26.46 t ha-1). It was observed that adoption of appropriate soil and crop management practices such as conservation tillage, good irrigation, incorporation of crop residues and application of manure etc. could enhance soil C pool by reducing existing carbon loss and promoting C accumulation in the soil.